An investigation into the relationships between technical collision behaviours and physical characteristics in world-class, international female rugby players - Woodhouse, L. N.; Bennett, M.; Tallent, J.; Patterson, S. D.; Waldron, M. (Journal of Sports Sciences, 2025)
This study first investigated how the probability of winning collision events is affected by technical characteristics among world-class, international female rugby union players, and second, whether enhanced performance of these technical characteristics was related to physical attributes. Carry and tackle events from 16 international matches played by a top-two world ranking team were coded according to technical characteristics and performance outcomes. Binary classification tree models revealed that carry performance was successfully predicted (p < 0.01) by combinations of the variables: carrier velocity at the line, change of direction and straightening angle, leg drive, body mass and system mass (carrier combined with assistance from team-mate(s)). Tackle performance was predicted by combinations of the variables: initial line-speed, tackle direction, tackle type, collision zone entry, body mass, system mass, arm use and leg drive. Cumulative link mixed effects models subsequently revealed that performance increases of ~2% in single-leg isometric squat, counter-movement jump, bench press, single-leg drop jump, 10 m acceleration momentum and velocity, and skinfolds and body mass; were associated with increasing and decreasing likelihoods of superior technical performance, depending on the investigated variable. These findings may increase the precision of practices, physical training and assessment methods, among elite-standard female rugby union players.